PENGABDIAN MASYARAKAT DENGAN KEGIATAN PENDIDIKAN KESEHATAN KEGAWATDARURATAN MATERNITAS UNTUK PENCEGAHAN KANKER ORGAN REPRODUKSI PADA REMAJA DI SMA SWASTA KEMALA BHAYANGKARI I MEDAN - Purwaningsih, Purwaningsih; Nisrina, Nisrina; Simamora, Endang Roswati; Surbakti, Claudia; Jadimanto, Jadimanto (MAJU : Indonesian Journal of Community Empowerment, 2025)
Adolescence is the age group between 10 and 19 years old and represents the transition from childhood to adulthood. Cancer is a disease that causes suffering and death in humans. It is the number one cause of death. Various preventative measures include increasing public awareness of the dangers of cancer, understanding healthy lifestyles, increasing interest in early cancer detection, research-based treatment, and participation in the National Health Insurance program so that all cases can be managed effectively. The purpose of this activity is to provide an initial effort to prevent reproductive organ cancer in adolescents and to increase knowledge at Kemala Bhayangkari I Private High School, Medan. The activity will take place on June 13, 2025, from 9:00 AM to 12:00 PM WIB, at Kemala Bhayangkari I Private High School, Medan. The method used is a group discussion, practice, and questionnaire. Activity Results Based on the results of the pretest questionnaire, the level of knowledge of participants was found to be in the good category for 10 people (33.3%), the sufficient category for 13 people (43.3%), and the less category for 7 people (23.3%). Meanwhile, based on the results of the posttest questionnaire, the level of knowledge of participants was found to be in the good category for 20 people (63.3%), the sufficient category for 7 people (23.3%), and the less category for 3 people (10%).